Abdominal wall hydrocele: A rare late postoperative complication of drain site wound incisional hernia - Edgar D. Sy; Yan-Shen Shan (Elsevier, 2015)
Late postoperative abdominal wall hydrocele is a rare complication following surgery. It may be form from a small untreated incisional hernia that passed through the musculo-aponeurotic layer of the abdominal wall. Diagnosis is easily made by clinical history of prolonged non-tender, non-reducible cystic mass below an incisional scar. Hydrocele should always be suspected when CT scan showed a fluid containing mass in the subcutaneous layer of abdominal wall with the presence of musculo-aponeurotic defect and absence incarcerate viscera in patient with chronic hypoalbuminemia. Surgical treatment should include total excision of hydrocele, facial repair and closure of hernia sac, preferably invertedly close into the abdominal cavity in order that the fluid secreting portion of the sac drained directly into in the abdominal cavity.